Maintenance planning framework for rock slopes management - Denysiuk, Roman (2021)
This paper presents a computational framework to assist in maintenance planning for geotechnical structures. The most suitable maintenance strategies are determined by optimization regarding the deterioration of structure and the cost of maintenance when satisfying constraints that translate demands for adequate levels of service. Uncertainties are accounted by considering model parameters as random variables. The framework is applied to the case study consisting in optimal maintenance planning for a highway slope belonging to the Portuguese network. The obtained results show the validity and usefulness of this framework. The framework can be also applied to different types of infrastructure assets.